Apakah Literasi Keuangan Dan Inovasi Digital Mampu Meningkatkan Kinerja UMKM Saat Menghadapi Covid – 19? - Pipin Fitriasari; Bobby Himawan; Maria Yanida; Arif Widyatama (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to examine the relationship between financial literacy and digital innovation on improving the performance of Micro, Small and Medium Enterprises (MSMEs). The research method used is a survey method. The number of respondents used was 56 respondents. The results of this study indicate that financial literacy and digital innovation have no relationship to the performance of MSMEs during the pandemic. Many factors cause this to happen, including the supporting components of the inadequate use of the technology, and many MSME owners who rely on their experience in running their business.